Role of Trade in Promoting Entrepreneurship Development between North East India and South East Asia (International Journal of Scientific Research and Management (IJSRM), 2017)
Entrepreneurship plays a vital role for economic growth and development of a nation or a region within the nation. Out of many important benefits of entrepreneurship development, generation of employment opportunities for job seekers is one of the most important issues. India‟s North Eastern Region (NER) is unique in terms of growth opportunities as it has the potential to develop into India‟s economic power house being a vibrant source of energy, oil, natural gas, coal, and limestone, besides being endowed with its largest perennial water system in the river Brahmaputra and its tributaries. Aptly considered as „The Gateway‟ to its South East Asian neigh bours, India‟s North East can emerge as a strategic base for foreign and domestic investors to tap into the South East Asian region, which is getting integrated through the operationalization of the South Asian Free Trade Agreement (SAFTA) and the Agreement on Trade in Services. At the initiative of the present Government at the center, the slogan of “Make in India” has gained immense popularity with a more vibrant “Act East Policy” now taking over the formerly „Look East Policy‟. The NER’s unlimited tourism opportunities, unique performing arts, and varied cuisine and handicrafts provides the ideal setting for its development as a hub for dealing in trade and commerce with India‟s eastern neighbours and boosting entrepreneurship. Development of NER will not only enhance the economy ofIndia but also will foster bilateral integration amongst the East and South East Asian neighbours. This paper therefore is an attempt to understand in what way will trade between the North East India and South East Asian regions can boost entrepreneurship and generate self employment.